2002
DOI: 10.4049/jimmunol.169.1.384
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL-10 Therapeutic Strategy Using the Immunomodulator AS101 in Protecting Mice from Sepsis-Induced Death: Dependence on Timing of Immunomodulating Intervention

Abstract: The role of IL-10 in experimental sepsis is controversial. The nontoxic immunomodulator, ammonium trichloro(dioxoethylene-o,o′)tellurate (AS101) has been previously shown to inhibit IL-10 expression at the transcriptional level. In this study, we show that in mice subjected to cecal ligation and puncture (CLP), treatment with AS101 12 h after, but not before, CLP significantly increased survival of septic mice. This was associated with a significant decrease in serum IL-10 and in IL-10 secretion by peritoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
93
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 43 publications
7
93
0
2
Order By: Relevance
“…In mice, plasma levels of IL-10 peak 12 hour after CLP, and the administration of neutralizing anti-IL-10 antibodies to mice with CLP increases mortality [40], suggesting that endogenous IL-10 prevents sepsis. In contrast, IL-10 exerts detrimental effects on bacterial clearance in the later period of sepsis and a nontoxic IL-10 inhibitor increases survival of septic mice [41][42][43]. In our experiments, NKT-cell-mediated IL-10 production by neutrophils enhances C5a generation via inhibition of CD55 expression on neutrophils during sepsis, which is consistent with our previous study [26].…”
Section: Discussionsupporting
confidence: 82%
“…In mice, plasma levels of IL-10 peak 12 hour after CLP, and the administration of neutralizing anti-IL-10 antibodies to mice with CLP increases mortality [40], suggesting that endogenous IL-10 prevents sepsis. In contrast, IL-10 exerts detrimental effects on bacterial clearance in the later period of sepsis and a nontoxic IL-10 inhibitor increases survival of septic mice [41][42][43]. In our experiments, NKT-cell-mediated IL-10 production by neutrophils enhances C5a generation via inhibition of CD55 expression on neutrophils during sepsis, which is consistent with our previous study [26].…”
Section: Discussionsupporting
confidence: 82%
“…The exogenous application of IL-10 can prevent septic shock in mice by inhibiting the synthesis of proinflammatory cytokines, while neutralizing IL-10 inhibited bacterial outgrowth in lungs and improved survival during murine pneumonitis [23,24]. Furthermore, recent studies demonstrated that sepsis is characterized by a biphasic immunological response: an initial hyperinflammatory phase, followed by a hypoinflammatory phase [25,26]. Therefore, it is quite likely that these contradictory observations were attributable to the time of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Most of its activities have been primarily attributed to the direct inhibition of the anti-inflammatory cytokine . This immunomodulatory property was found to be crucial for the clinical activities of AS101, demonstrating the protective effects of AS101 in parasite and viralinfected mice models (18), in autoimmune diseases (19), in septic mice (20), and in a variety of tumor models in mice and humans where AS101 had a clear anti-tumoral effect (21)(22)(23). More importantly, AS101 was previously shown to delay the onset of autoimmune manifestations in a murine model of lupus erythematosus, reduce the level of immune complex deposition in the glomeruli, reduce proteinuria, prevent glomerular hypercellularity and mesangial expansion, and reduce the mean glomerular volume of treated mice (19).…”
mentioning
confidence: 99%